Peran Biostarter EM-4 dan Feses Kuda terhadap Kualitas Biogas dari Serat Ampas Tebu - Auzha Hira Asfaha; Yenni Darvina (Lembaga Yasin AlSys, 2025)
The rising global demand for energy, particularly from fossil fuel sources, has triggered an energy crisis that necessitates the exploration of alternative solutions. One promising effort is the utilization of renewable energy in the form of biogas, which can be produced from agricultural waste such as sugarcane bagasse and livestock waste such as horse manure. This study aims to analyze the effects of horse manure and the EM-4 biostarter on the quality of the biogas produced. An experimental method was employed using a batch-type digester reactor with three different feedstock compositions: 50% sugarcane bagasse (SB):50% horse manure (HM), 40%SB:60%HM, and 30%SB:70%HM. The parameters observed included initial and final pH, gas pressure, gas temperature, and flame color testing. The results show that the addition of EM-4 biostarter accelerates the gas formation process, yields higher gas pressure, and improves the overall quality of the biogas. Moreover, increasing the proportion of horse manure enhances the decomposition of sugarcane fibers, leading to greater gas volume production. The study concludes that the optimal combination of horse manure and EM-4 biostarter is effective in improving both the quality and quantity of biogas, while supporting waste utilization as a renewable energy source. The practical implications of these findings emphasize the importance of managing the digester environment safely to prevent leakage and external disturbances during biogas production.